From green promises to measurable results? Who wins and who lags in the green transition race - Lobonț, Oana Ramona; Brândaş, Claudiu; Doraș Lisnic, Anastasia; Criste, Cristina; Cristescu, Marian-Pompiliu (Frontiers in Environmental Science, 2026)
This study starts from the understanding that green finance is a central pillar of the green transition in the European Union, in which green finance is not just a financial instrument, but the mechanism through which both public capital (government or European funds) and private capital (banks, investors, companies) are directed towards projects that support environmental and sustainability objectives. The proposed research assesses which EU Member States perform best in the field of green finance and identifies the structural factors underlying these differences, using a composite index based on the entropy method. The index integrates eight indicators that capture financial effort and environmental outcomes, specifically green investments as a share of GDP, renewable energy share, environmental taxes, greenhouse gas intensity of the economy, Environmental Performance Index, green transport, protected areas, and waste generated per capita. Official international data sources, including Eurostat, the European Environment Agency, the World Bank, and Yale University, were utilized for all variables in 2023. All indicators were normalized, and weights were assigned objectively using the entropy method to ensure comparability and reduce subjective bias. The results show wide disparities across the European Union. Sweden, Denmark, Finland, and Lithuania form the leading group due to high levels of green investment, strong renewable energy profiles, and low greenhouse gas intensity. Large industrial economies such as Germany and Italy score lower because their high emission levels outweigh the effect of existing environmental measures. Smaller and service-oriented economies, such as Luxembourg and Malta, perform relatively well due to their moderate emissions and balanced environmental outcomes. At the opposite end, Bulgaria, Cyprus, and Czechia record the weakest results, shaped by carbon-intensive economic structures and limited green investment. These findings suggest that the interaction between financial commitment and structural characteristics, such as the energy mix and emission intensity, strongly influences performance in green finance. Strengthening green investment flows and accelerating emission reduction efforts remain essential for convergence across the EU. Tailoring national green finance strategies to each country’s structural profile can increase the effectiveness of financial instruments and support progress towards the objectives of the European Green Deal.